Analisis Kandungan Merkuri Pada Krim Pemutih Yang Beredar Di Kota Manado - Parengkuan, Kissi; Fatimawali, Fatimawali; Citraningtyas, Gayatri (PHARMACON, 2013)
ABSTRACT Whitening cream is a mix of chemicals which whiten skin or bleach black fleck on the skin. The use of Mercury in whitening cream effects many things, such as skin color changes, and at the end cause black flecks, allergy, and irritation. The use of high dose cause permanent brain damage and cancer. The objectives of this research were to identify and determine Mercury (Hg) in some whitening creams marketed in Manado City.Sample of whitening cream were 10 samples.Identification of Mercury using color test, and Cold Vapour-Atomic Absorption Spectrophotometry (CVAAS). The results shows that five samples contains Mercury (Hg)0,0004 ppm, 0,0003 ppm, 0,0006 ppm, 0,0004 ppm, and 0,0005 ppmwithin ten samples analysis. Key words : Whitening cream, Mercury, CV-AAS (Cold Vapour Atomic AbsorbtionSpectrophotometry).